Hemorrhagic Colitis Caused by Everolimus in a Patient with Nonfunctional Pancreatic Neuroendocrine Neoplasms: A Case Report - Noriyuki Arakawa; Atsushi Irisawa; Kazuyuki Ishida; Takuya Tsunoda; Yoshiko Yamaguchi; Akane Yamabe; Makoto Eizuka; Shunzo Tokioka; Hiroto Wakabayashi (Medicina, 2022)
A 60-year-old woman was diagnosed with nonfunctional pancreatic neuroendocrine neoplasm with multiple liver metastases and was administered everolimus. Due to persistent epigastric pain and diarrhea, a colonoscopy was performed on the 14th day after the start of everolimus administration, which revealed small bleeding ulcers in the ileocecal region, transverse colon, and rectum. These adverse effects were attributed to the everolimus; it was immediately discontinued, and the patient’s clinical symptoms and imaging findings improved. We concurred that the administration of calcium channel blockers resulted in the inhibition of everolimus metabolism and the disease onset. The everolimus was discontinued. There was no subsequent recurrence of hemorrhagic colitis.